The Right to Work and Artificial Intelligence (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article states that artificial intelligence technologies are becoming increasingly integrated into everyday life, leading to their growing influence on various areas of human activity. It is noted that the use of artificial intelligence has a significant impact on the labour market, increasing the efficiency of labour utilisation. The use of artificial intelligence is transforming work processes, as it significantly increases the speed of labour-intensive tasks related to data analysis and exchange. As a result, employees are beginning to perform tasks at a higher intellectual level, focusing their attention on strategic goals. At the same time, it is observed that with changes in the labour market, artificial intelligence can lead to changes in professions and job losses. It is indicated that there is a global shortage of specialists in the field of artificial intelligence, as the training, retraining and upskilling of employees cannot keep pace with demand. It is predicted that over the next ten years, the number of jobs in the technology sector will grow twice as fast as the total workforce.It is emphasised that there is no consensus in scientific discussions on the benefits or threats of artificial intelligence in the field of labour rights compliance. It is proved that the spread of artificial intelligence technologies is inevitable, therefore it is necessary to introduce clear principles for its use, taking into account human rights, in particular the right to work. The provisions of Regulation (EU) 2024/1689 – the Artificial Intelligence Act – regarding guarantees for the observance of human rights are disclosed. The reservations established in the Regulation regarding the possible high degree of risk of using artificial intelligence in the field of employment, recruitment, management and promotion of employees are highlighted.It is argued that the Ukrainian government is paying attention to the development of artificial intelligence and has developed several programmes for its implementation, but these do not take into account aspects of labour rights and employment. It is underlined that compliance with international and European human rights standards, in particular labour rights, is one of the important conditions for Ukraine to become a full member of the European Union. The need to strengthen training of employees in the use of artificial intelligence skills and to invest in modern technologies in order to fully exploit its advantages is outlined.